When Strangers Marry - Kleypas, Lisa (New York Avon Books, 2002)
Lysette buried her face against Max's throat. "But he's going to take me away. Don't let him, don't -- "</ "You're not going anywhere," Max interrupted. "Calm yourself, Lysette. It's not good for you to become excited." His possessiveness made her strangely giddy. As far as he was concerned, she was his, and no one was going to take her away from him.</ Max stared at Etienne. His voice was soft, but it contained a note that chilled Lysette's blood. "If you so much as disarrange a hair on her head, I'll tear you apart."</ Lysette couldn't believe it, but she didn't care about her ruined reputation. The only thing that mattered was that she wouldn't have to marry Etienne.
Keywords: Romance fiction